2006
DOI: 10.1161/01.hyp.0000229648.67883.f9
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type-2 Receptor Stimulation Prevents Neural Damage by Transcriptional Activation of Methyl Methanesulfonate Sensitive 2

Abstract: Abstract-The molecular mechanisms of the contribution of angiotensin II type-1 receptor blockers to neuronal protection are still unclear. Here, we investigated the effect of angiotensin II type-2 (AT 2 ) receptor stimulation on neurons and cognitive function involving a new neuroprotective factor, methyl methanesulfonate sensitive 2 (MMS2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 50 publications
4
90
0
1
Order By: Relevance
“…Li et al (2005) reported that AT 2 receptor stimulation enhanced neuronal survival and neurite outgrowth in response to ischemia-induced neuronal injury. We previously showed that AT 2 receptor stimulation enhanced neural differentiation and the repair of damaged DNA by induction of a neural-differentiating factor, methyl methanesulfonate sensitive-2, which is one of the ubiquitin-conjugating enzyme variants (Mogi et al, 2006). In this study, we observed that direct stimulation of the AT 2 receptor enhanced neurite elongation in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 49%
“…Li et al (2005) reported that AT 2 receptor stimulation enhanced neuronal survival and neurite outgrowth in response to ischemia-induced neuronal injury. We previously showed that AT 2 receptor stimulation enhanced neural differentiation and the repair of damaged DNA by induction of a neural-differentiating factor, methyl methanesulfonate sensitive-2, which is one of the ubiquitin-conjugating enzyme variants (Mogi et al, 2006). In this study, we observed that direct stimulation of the AT 2 receptor enhanced neurite elongation in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 49%
“…6 Although it is thought that Ang II does not cross the blood-brain barrier, it has been reported that all RAS components exist in the central nervous system, suggesting that Ang II is produced and functions in the central nervous system. There is no doubt that lowering blood pressure is one of the most recommended therapeutic approaches for the prevention of stroke.…”
Section: Stroke Preventionmentioning
confidence: 99%
“…We also showed that AT 2 receptors enhance neural differentiation and the repair of damaged DNA by induction of the neural differentiating factor MMS2 (methyl methane sulfonate sensitive-2), which is one of the ubiquitin-conjugating enzyme variants. 6 PREVENTION OF METABOLIC SYNDROME-INDUCED DEMENTIA Continuous activation of the brain RAS impairs cognitive function through stimulation of the AT 1 receptor. 23 The ARB candesartan ameliorates impaired cognitive function in mice with type 2 diabetes (KKAy), at least partly, because of increased expression of MMS2 and an improvement in glucose intolerance.…”
Section: Enhancement Of Neural Differentiationmentioning
confidence: 99%
“…7 Recently, experimental and clinical studies have reported that cerebral ischemic injury and cognitive function can be ameliorated by inhibition of renin-angiotensin system. [8][9][10] Additionally, brain Ang II is upregulated both in cerebral ischemia and Alzheimer's disease and can be regulated with systemic angiotensin type 1 (AT1) receptor blocker (ARB) treatment. 9,11,12 Thus, Ang II-induced astrocyte senescence may be involved in the pathology of cerebral ischemic injury and age-associated neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%